The Impact of Web 2.0 Tools on Children’s Vocabulary Acquisition: A Quasi-Experimental Study - Saydam, Cansu; Dikme, Berivan; Tekin, Serdar (Fırat University, 2025)
In line with the immense developments in technology recently, Web 2.0 tools have been prevalently adopted and used in language education both in intramural and extramural settings. Previous research mostly investigated this issue from various perspectives, including learners’ and teachers' attitudes, learners’ motivations, focusing mostly on older learner settings such as high schools and tertiary education. Focusing on young learners, an under-researched area in language education, this study examines the effect of use of Web 2.0 tools on learners’ English vocabulary attainment through quasi-experimental method. A pre-test was applied to both control and experimental groups, consisting of 20 small children studying in the 2nd grade (eight year olds) which was followed a 4-week intervention of teaching the same topics with and without the use of Web 2.0 tools, and finally a post-test was applied to both groups. Findings revealed that the scores of experimental group were far better than those of control group, indicating that Web 2.0 tools had a positive impact on their vocabulary acquisition. Pedagogical implications are provided for young learner education based on the findings of this study.

Son zamanlarda teknolojideki hızlı gelişmelere paralel olarak, Web 2.0 araçları hem okul içi hem de okul dışı ortamlarda dil eğitiminde yaygın olarak benimsenmiş ve kullanılmaktadır. Daha önce yapılan araştırmalar çoğunlukla bu konuyu öğrencilerin ve öğretmenlerin tutumları, öğrencilerin motivasyonları dahil olmak üzere çeşitli bakış açılarından incelemiş ve çoğunlukla lise ve üçüncül eğitim gibi daha büyük öğrenci ortamlarına odaklanmıştır. Dil eğitiminde yeterince araştırılmamış bir alan olan küçük öocuklara odaklanan bu çalışma, yarı deneysel yöntemle Web 2.0 araçlarının kullanımının öğrencilerin İngilizce kelime dağarcığına olan etkisini incelemektedir. 2. sınıfta (sekiz yaş) okuyan 20 küçük çocuktan oluşan kontrol ve deney gruplarına bir ön test uygulanmış, ardından aynı konuların Web 2.0 araçları kullanılarak ve kullanılmadan öğretildiği 4 haftalık bir uygulama yapılmış ve son olarak her iki gruba da bir son test uygulanmıştır. Bulgular, deney grubunun puanlarının kontrol grubundan çok daha iyi olduğunu ortaya koymuş ve bu da Web 2.0 araçlarının kelime dağarcığı edinimleri üzerinde olumlu bir etkisi olduğunu göstermiştir. Bu çalışmanın bulgularına dayanarak küçük çocukların dil eğitimine yönelik pedagojik çıkarımlar sunulmaktadır.
Web 2.0 Araçlarının Çocukların Kelime Dağarcığı Edinimi Üzerindeki Etkisi: Yarı Deneysel Bir Çalışma
Keywords: Applied Linguistics and Educational Linguistics; Uygulamalı Dilbilim ve Eğitim Dilbilimi; Child Development Education; Çocuk Gelişimi Eğitimi; Educational Technology and Computing; Eğitim Teknolojisi ve Bilgi İşlem